2015
DOI: 10.1063/1.4907974
|View full text |Cite
|
Sign up to set email alerts
|

In situ measurement of fixed charge evolution at silicon surfaces during atomic layer deposition

Abstract: Interfacial fixed charge or interfacial dipoles are present at many semiconductor-dielectric interfaces and have important effects upon device behavior, yet the chemical origins of these electrostatic phenomena are not fully understood. We report the measurement of changes in Si channel conduction in situ during atomic layer deposition (ALD) of aluminum oxide using trimethylaluminum and water to probe changes in surface electrostatics. Current-voltage data were acquired continually before, during, and after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Water is a particularly common solvent in the synthesis process, biosensor, and the electrode of light-emitting and solar cells for Si QDs. Many recent experimental studies have shown that water-induced field effect, which caused the change of electrical conductivity of hydrogen-terminated silicon substrates. Furthermore, the photoluminescence (PL) spectra of silicon surface affected by water vapor can be used as a humidity sensor, , and Si QDs used as the electrode in light-emitting or solar cells are susceptible to degradation by water vapor. , Therefore, a critical fundamental question for Si QDs is whether and how the electronic structure and hence the PL properties is altered on the nanoscale, in particular, with the presence of water.…”
mentioning
confidence: 99%
“…Water is a particularly common solvent in the synthesis process, biosensor, and the electrode of light-emitting and solar cells for Si QDs. Many recent experimental studies have shown that water-induced field effect, which caused the change of electrical conductivity of hydrogen-terminated silicon substrates. Furthermore, the photoluminescence (PL) spectra of silicon surface affected by water vapor can be used as a humidity sensor, , and Si QDs used as the electrode in light-emitting or solar cells are susceptible to degradation by water vapor. , Therefore, a critical fundamental question for Si QDs is whether and how the electronic structure and hence the PL properties is altered on the nanoscale, in particular, with the presence of water.…”
mentioning
confidence: 99%
“…Further, this charge has been shown using MOSCAP structures to exist entirely at the SiO x –Al 2 O 3 interface, not in the bulk of the amorphous alumina film . Also, the N F may form during the creation of the first alumina layer during ALD . Corona charging, and second harmonic generation measurements of annealed alumina films on Si indicate that the N F observed in thicker MOSCAPs also exists in thin layers ( t ox < 3 nm) that may be useful for MIS tunnel diodes or ohmic contacts.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] For instance, the electrical conductivity of thin film coatings composed of oxygenterminated Si QDs under a water vapor atmosphere may be increased by a factor of four due to the adsorption of water molecules on the thin films. 11,12 Furthermore, Si QDs were applied as a humidity sensor as the photoluminescence (PL) intensity of porous Si QDs descended as relative humidity rose, [13][14][15] which may arise from the PL weakly quenched by water with large dipole moments. 16 According to the previous studies from the National Renewable Energy Laboratory (NREL), one of the severe factors accelerating the light-induced degradation process is the effect of a humid environment on the Sibased photovoltaic module.…”
Section: Introductionmentioning
confidence: 99%